(untitled) - Murdock, Kelly L. (Boston, MA, 2006)
Get ready to uncover all that Maya 7 has to offer! Giving you a firm foundation, Maya 7 Revealed allows you to master concepts on both a technical and an artistic level. Begin by examining the concept behind each task-the goal and the necessary features that are involved. Then go in-depth with the objective of your task as you study examples and learn the steps necessary to complete it. Working your way through the comprehensive, step-by-step lessons, you’ll develop the confidence you need to create incredible animations using Maya 7.
Keywords: Includes index,Computer graphics,Digital art,Computer animation,Three-dimensional display systems,Mỹ thuật số,Đồ họa vi tính